2022
DOI: 10.1002/1873-3468.14434
|View full text |Cite
|
Sign up to set email alerts
|

The cyclin‐dependent kinase inhibitor p27Kip1 interacts with the aryl hydrocarbon receptor and negatively regulates its transcriptional activity

Abstract: Edited by Ivan Sadowski p27 Kip1 functions to coordinate cell cycle progression through the inhibition of cyclin-dependent kinase (CDK) complexes. p27 Kip1 also exerts distinct activities beyond CDK-inhibition, including functioning as a transcriptional regulator. The aryl hydrocarbon receptor (AhR) is a ligand-activated transcription factor with diverse biological roles. The regulatory inputs that control AhRmediated transcriptional responses are an active area of investigation. AhR was previously established… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 68 publications
1
6
0
Order By: Relevance
“…For p27 Kip1 , protein expression was increased by either HG or exogenous H 2 O 2 , but neither of them influenced the gene expression of p27 Kip1 . Elson et al ( 13 ) demonstrated that in most situations, the gene expression of p27 is consistent in the cell cycle, indicating that the alteration of p27 occurs at the protein level, corresponding to our results. In a study on diabetic nephropathy, Aitken et al ( 14 ) demonstrated that HG inhibits cell proliferation (cell growth) in a dose-dependent manner, which is associated with the increased expression of p27 Kip1 .…”
Section: Discussionsupporting
confidence: 90%
“…For p27 Kip1 , protein expression was increased by either HG or exogenous H 2 O 2 , but neither of them influenced the gene expression of p27 Kip1 . Elson et al ( 13 ) demonstrated that in most situations, the gene expression of p27 is consistent in the cell cycle, indicating that the alteration of p27 occurs at the protein level, corresponding to our results. In a study on diabetic nephropathy, Aitken et al ( 14 ) demonstrated that HG inhibits cell proliferation (cell growth) in a dose-dependent manner, which is associated with the increased expression of p27 Kip1 .…”
Section: Discussionsupporting
confidence: 90%
“…We previously reported p27 Kip1 as a target gene of the AhR in hepatoma cells [58]. Furthermore, recently we identified a new regulatory cross-talk between p27 Kip1 and the AhR [59]. CABLES1 is a newly identified CDK inhibitor that has been demonstrated to play important roles in cell cycle regulation and suppression of tumour growth [60][61][62][63].…”
Section: Discussionmentioning
confidence: 99%
“…This can be mediated by increased expression of the p27 Kip1 cyclin-dependent kinase inhibitor or via further interactions of the AhR with Rb protein [ 66 ]. The relationship between the AhR and cell cycle regulators can be bi-directional, as both Rb and p27 Kip1 have been shown to regulate the AhR-mediated transcription [ 67 , 68 ]. Here, we found that the AhR antagonist CH-223191 inhibited the proliferation of HT-29 and HCT116 cells (in a similar manner as AhR KO), which seems to provide further support to the hypothesis that the AhR plays a positive role in the control of colon cancer cell proliferation, perhaps in a similar manner as in the above discussed models of liver carcinoma cells.…”
Section: Discussionmentioning
confidence: 99%